Acid attacks: Broadening the multidisciplinary team to improve outcomes. Issue 3 (May 2020) - Song, Marie; Armstrong, Alexander; Murray, Alexandra
Highlights: Corrosive substance attacks continues to be a rising issue on a global scale. Common motivations for acid attacks include hate crimes, gangs in retribution, 'honour based violence', racism, domestic abuse and armed robbery. Media sensationalisation of acid attacks in the past few years has occurred the number of treated cases did not correlate with reports in the Freedom of Information request. Public empowerment as first responders and close collaboration with emergency services, media and government can help to improve overall patient care. Abstract: A rise in the current trend of corrosive substance attacks have been reported in the UK, causing devastating effects on victims. The optimal management of these patients requires the specialist skills of the burn multidisciplinary team (MDT) to address the resulting physical and psychological trauma experienced. However, burn care must commence in the pre-hospital setting. The public and first responders are invaluable resources in helping to limit the adverse effects of burns. Challenges of burn care outside the Burns Unit are not limited to the treatment of the injured patient and the rehabilitation of survivors. These challenges also encompass better education of the public and allied health professionals, as well as planning strategies to reduce the incidence of acid attacks. Prevention is always better than cure. This paper discusses the broadening of the MDT to improve outcomes in acid attacks by exploring the wider roles of the public, media, emergency services, police, legislation and better education.